Peran Arus Kas Dan Rasio Keuangan Dalam Memprediksi Financial Distress Pada Perusahaan Manufaktur Yang Terdaftar Di Bursa Efek Indonesia - Ananda Budi Wuriani; M. G. Kentris Indarti (Universitas Sains dan Teknologi Komputer, 2025)
This study aims to analyze the role of cash flow and financial ratios in predicting financial distress in manufacturing companies listed on the Indonesia Stock Exchange for the period 2021–2023. The independent variables include cash flow, profitability, liquidity, leverage, and activity ratios, while financial distress serves as the dependent variable. This research employs logistic regression analysis with purposive sampling, resulting in a sample of 100 companies with a total of 300 observations. The findings reveal that liquidity and activity ratios have a significant negative effect on financial distress, while solvency has a significant positive impact. However, cash flow and profitability do not significantly influence financial distress. These findings highlight the importance of liquidity management and asset efficiency in reducing financial distress risk, while also indicating that high debt burdens increase the likelihood of financial distress. The study’s implications provide valuable insights for management and investors in making strategic financial decisions